Study protocol for a randomized controlled trial of Regulating Together (RT), a group therapy for emotion dysregulation in school-age autistic youth and their caregivers - Walker S. McKinney; Lauren J. Tadevich; Lauren M. Schmitt; Paul S. Horn; Jennnifer R. Ruberg; Susan W. White; Debra L. Reisinger; Karen W. Burkett; Shivali Sarawgi; Sungeun Kang; Rebecca C. Shaffer (BMC Psychology)
Abstract Background Emotion dysregulation is a common concern in autistic youth. Growing evidence suggests emotion dysregulation underlies multiple co-occurring issues in autism, including externalizing (e.g., aggression, irritability) and internalizing (e.g., anxiety, depression) disorders, and thus may serve as a key transdiagnostic treatment target. Emotion dysregulation during middle childhood (8–12 years) is concurrently and longitudinally associated with social difficulties and poorer quality of life for autistic individuals, highlighting a key window for intervention. There is an urgent need for treatments for emotion dysregulation in school-age autistic youth that involve caregivers to maximize skill generalization. To address this need, our group developed Regulating Together, an intensive outpatient group program targeting emotion dysregulation in 8- to 12-year-old autistic youth that integrates strategies from cognitive behavioral therapy, mindfulness and acceptance-based therapies, and parent training programs. Building on our previous non-randomized trials of Regulating Together, we document the study protocol for our first, and ongoing, randomized controlled trial comparing Regulating Together to an active control condition. Methods This is a five-year randomized controlled trial comparing Regulating Together to Achieving Independence and Mastery in School (AIMS), an active control condition targeting executive functioning difficulties, in an outpatient hospital setting. Enrollment is ongoing and the study is expected to be completed in late Fall of 2026. Participants will be 144 autistic youth (8–12 years; IQ ≥ 65) randomized to either 5-week treatment condition. A comprehensive assessment battery integrating self-, caregiver-, and clinician-report information, functional outcomes (i.e., number of psychiatric hospitalizations), objective outcomes (probabilistic reversal learning task), and biobehavioral measures (heart rate variability) will be collected and compared between baseline (Week 0), post-treatment (Week 7), post-generalization (Week 16), and at long-term follow-up (Week 29). Discussion This is the first comparison of the Regulating Together program to an active treatment condition. Findings from this study will build on previous piloted iterations of Regulating Together by characterizing its efficacy in relation to active treatment, testing moderators of treatment response, and identifying barriers and facilitators to treatment access, impact, and sustainability. Following completion of this study, we will pursue implementation studies (e.g., testing program implementation and effectiveness in community settings). Dissemination and external provider training efforts are ongoing. Trial registration Trial registration took place through ClinicalTrials.gov (NCT05803369) on March 14th, 2023.